2020
DOI: 10.1002/fsn3.1660
|View full text |Cite
|
Sign up to set email alerts
|

Application of essential oil of Pistacia atlantica Gum, polypropylene and silica nanoparticles as a new milk packaging

Abstract: The aim of current study was to investigate the antimicrobial effect of gum essential oil of Pistacia atlantica (wild pistachio) tree (GEO) and design a new film based on polypropylene polymer coated with silica nanoparticles and GEO. The antimicrobial activity of the packaging film was evaluated with or without milk on Staphylococcus aureus, Salmonella enterica, Escherichia coli, and Listeria monocytogenes during 35 days. The results showed that GEO has significant antibacterial properties. It was most effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…GEO was released more quickly from a film devoid of NPs, thus reducing the shelf life of packaged foods. The shelf life of milk was prolonged by 35 days due to the developed antibacterial active packaging [ 184 ]. Zhu et al fabricated a food packaging film using polylactic acid and mesoporous silica nanoparticles loaded with clove essential oil (PMC films) by means of a solvent volatilization method.…”
Section: Nanoparticles As Carriers Of Eomentioning
confidence: 99%
“…GEO was released more quickly from a film devoid of NPs, thus reducing the shelf life of packaged foods. The shelf life of milk was prolonged by 35 days due to the developed antibacterial active packaging [ 184 ]. Zhu et al fabricated a food packaging film using polylactic acid and mesoporous silica nanoparticles loaded with clove essential oil (PMC films) by means of a solvent volatilization method.…”
Section: Nanoparticles As Carriers Of Eomentioning
confidence: 99%
“…The antibacterial activity of the produced packing film containing 0.001 g of silica nanoparticle encapsulating GEO had a greater inhibitory impact (3.45 log CFU/g) against S. aureus , S. enterica , E. coli , and L. monocytogenes , while a package without silica nanoparticles exerted no antibacterial activity. The shelf life of milk was extended by 35 days due to the extended release of GEO from nanoparticles [ 63 ].…”
Section: Antimicrobial Nanocomposites Nanomaterials Used For Active P...mentioning
confidence: 99%
“…The surface-functionalized nanoparticles were further shown to decrease the oxygen permeability by 44% compared to the pure PLA films. Ellahi et al also concluded that silica nanoparticles can sustain the release of Pistacia atlantica gum essential oil from a PP film [ 139 ]. The PP polymer was coated with silica nanoparticles and the essential oil.…”
Section: Active Nanocomposite Filmsmentioning
confidence: 99%